2019
DOI: 10.1038/s41467-019-13365-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variance of spring phenology in temperate deciduous forests is constrained by background climatic conditions

Abstract: Leaf unfolding in temperate forests is driven by spring temperature, but little is known about the spatial variance of that temperature dependency. Here we use in situ leaf unfolding observations for eight deciduous tree species to show that the two factors that control chilling (number of cold days) and heat requirement (growing degree days at leaf unfolding, GDDreq) only explain 30% of the spatial variance of leaf unfolding. Radiation and aridity differences among sites together explain 10% of the spatial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 61 publications
4
70
0
Order By: Relevance
“…The decreasing variation suggests that forest ecosystems were relatively stable during the past several decades. This pattern suggests that the variation of forest ecosystem greenup is mainly driven by temperature, although the impacts of ecological factors light availability, species and tree size 73 , 74 need to be investigated in the future. However, opposite trends in interannual variations were found for greenup onset and spring temperature; this mainly occurred in the Rocky Mountain area.…”
Section: Discussionmentioning
confidence: 99%
“…The decreasing variation suggests that forest ecosystems were relatively stable during the past several decades. This pattern suggests that the variation of forest ecosystem greenup is mainly driven by temperature, although the impacts of ecological factors light availability, species and tree size 73 , 74 need to be investigated in the future. However, opposite trends in interannual variations were found for greenup onset and spring temperature; this mainly occurred in the Rocky Mountain area.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, however, have suggested that subfreezing temperatures were effective 36 , 37 , so we also tested chilling models using −10 °C as the lower limit. Many studies have also assumed that freezing temperatures did not contribute to winter CA and only included temperatures >0 °C for calculating CA 11 , 38 . Models C 1 –C 6 were developed based on various combinations of the upper and lower temperature limits.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal requirements strongly regulate vegetative and reproductive plant development in deciduous forest tree species (Peaucelle et al, 2019;Picornell et al, 2019). The mid-latitudes climate is characterized by successive favorable and non-favorable periods related to a marked seasonality.…”
Section: Introductionmentioning
confidence: 99%